Two-Wheel Tractor Performance Test With Variations Of Soil Trilling Patterns In Rice Land, East Lombok - Riza Hamkary Salam; Muhammad Yul Fikry; Mai Rizali (Ecobios Journal Of Environmental Science, 2024)
The purpose of this experiment was to determine the effect of variations in soil cultivation patterns on the performance of two-wheeled tractor plows in rice fields. The research experiment was conducted in Kotaraja Village, Sikur District, East Lombok Regency. The type of soil at the location is clay textured with an area of 0.09 Hg. The research was carried out in January 2022. The method used in this study was an experimental method with a Completely Randomized Design (CRD) which was repeated three times. The experimental activities were carried out by comparing variations in soil cultivation patterns (a. Edge cultivation pattern, b. Middle cultivation pattern and c. Close alternating cultivation pattern) on rice fields so that different effects were obtained from each soil cultivation pattern. The research parameters observed were fuel requirements, work speed, and soil cultivation efficiency. Based on the results and discussions, several conclusions can be put forward, namely that the land cultivation pattern has an effect but is not significant on speed, fuel consumption, theoretical field capacity, effective field capacity and field efficiency. In addition, the edge pattern has a high working speed of 1.27 m/s and a processing time of 0.16 hours and more efficient fuel consumption compared to other patterns, namely 2.25 L/hour. The field efficiency value of the three soil processing patterns is relatively low, ranging from 34.30% to 52.04%. Therefore, in this study, it is recommended to use the edge pattern as an effective and efficient method in soil processing.